Swedish Plectida (Nematoda). Part 8. The genus Onchium Cobb, 1920 - Holovachov, Oleksandr (Zootaxa, 2015)
Four known and one new species of Onchium are described from bottom sediments collected in Skagerrak off the west coast of Sweden. The following known species are redescribed: Onchium ocellatum Cobb, 1920, O. metocellatum Wieser, 1956, O. parocellatum (Allgén, 1940) and O. robustum Gerlach, 1965. Onchium longispiculum sp. n. is characterised by the 1.34–1.77 mm long body, anterior body end without cephalic capsule, anteriormost somatic sensilla located posterior to onchiostyle base, ocelli absent, excretory pore located at basis of lips, onchiostyle uniformly cylindrical, alveolar supplements indistinct, tubular supplements absent, spicules arcuate and 44–65 µm long. The new species has a unique set of characters (absence of developed ocelli and very long somewhat asymmetrical spicules) separating it from all other known species of the genus Onchium. The following nomenclatorial changes are proposed: O. conicaudatum (Allgén, 1935) is considered a junior synonym of O. metocellatum; O. conicaudatum apud Wieser, 1951 is considered a synonym of O. minutum Kito, 1981. The diagnosis of the genus Onchium is emended and a tabular compendium and dichotomous identification key to species of the genus Onchium are provided.